Evaluation of the Effectiveness of Baselines and Thresholds Intensity Epidemics, According to the Results of Traditional Surveillance for Influenza - L. S. Karpova; A. A. Sominina; D. M. Danilenko; K. M. Volik; V. N. Leonenko (Эпидемиология и вакцинопрофилактика)
Relevance. Early recognition of the beginning of the epidemic in the country and its individual Federal Districts determines the possibility of timely introduction of anti-epidemic measures in the country as a whole and at the regional level, which helps to reduce the incidence rate and socio-economic damage from influenza. The aim of the study was to improve the traditional surveillance of influenza and common cold in Russia in accordance with the requirements of the World Health Organization. Materials and methods. Weekly epidemic thresholds (NEP), as well as baseline (BL) and epidemic intensity thresholds, were calculated on average for the entire population of the cities and individual federal districts observed. Results and discussion. For the first time, as an additional criterion of the epidemic and its intensity, the baselines and intensity thresholds for the incidence of «influenza» and hospitalization with a diagnosis of «influenza» for the entire population and different age groups of the Russian Federation and the total incidence of influenza and ARI at the regional level were calculated and tested. Epidemic 2019, in terms of the total incidence of influenza and ARI, separately «influenza» and hospitalization with a diagnosis of «influenza», was average in terms of intensity, as the previous (2018). The baselines and thresholds of the intensity of the epidemic on the total incidence of influenza and ARI for the Federal districts and, in addition, separately influenza for different age groups of the population of the country revealed the order of involvement in the epidemic and the different intensity of the epidemic in the Federal districts and age groups. This season in the country as a whole at the beginning of the epidemic was more sensitive weekly epidemic threshold, and at the end – post epidemic baseline of influenza and ARI. Сonclusion. The baseline incidence of «influenza» and a hospitalization with a diagnosis of «influenza» was more sensitive than the weekly epidemic thresholds and the baseline cumulative incidence. Baseline «influenza» morbidity and hospitalization with a diagnosis of «influenza» may be additional signs of the epidemic, revealing the initial and residual circulation ofinfluenza, mainly at a sporadic level.